SUBSET OF NANDA-I NURSING DIAGNOSES FOR INTENSIVE CARE: DELPHI TECHNIQUE AND FOCUS GROUP - Mirko Masciullo; Flavio Marti; Antonello Cocchieri; Lucia Mitello; Andrea Fidanza; Anna Rita Marucci (NSC Nursing)
Introduction: The NANDA-I taxonomy classifies nursing diagnoses to standardise communication and illustrate the impact of nursing on health outcomes. To improve usability in clinical practice, subsets of diagnoses, interventions, and outcomes have been developed for specific healthcare settings. These subsets facilitate documentation and decision making while supporting, rather than replacing, the clinical judgment of the nurse. Objective: The study aims to develop a Subset of NANDA-I Nursing Diagnoses that nurses consider relevant in an intensive care setting. Materials and Methods: A two-round Delphi study was carried out at the A.O. San Camillo Forlanini of Rome to identify the most appropriate diagnoses to constitute the Subset. Using the Delphi technique, two anonymous online questionnaires were submitted to a group of 10 experts. The nurses involved expressed their level of consensus on each of the most used NANDA-I diagnoses in intensive care. Results: Nurses evaluated a total of 51 NANDA-I nursing diagnoses using 5-level Likert scales, including 47 diagnoses in the Subset. The most representative ones were: "(00004) Risk of infection", "(00047) Risk of compromised skin integrity", "(00030) Compromised gas exchange", "(00091) Compromised mobility in bed", "(00198) Model of disturbed sleep", "(00249) Risk of pressure injury in adults". Conclusion: Among the included diagnoses, "Risk of infection" received unanimous agreement, confirming its essential role in intensive care. Other highly rated diagnoses, such as "Risk of compromised skin integrity," "Impaired gas exchange," and "Deficit in Self-Care: Bathroom," aligns with findings from previous studies. Some diagnoses, including "Compromised mobility in bed" and "Disturbed sleep pattern," were less commonly used in other ICUs, but were considered highly relevant by Delphi participants. The results highlight the focus of nurses on infection prevention, hygiene, gas exchange, pain management, mobilisation, and prevention of pressure injury. In particular, diagnoses related to stress, family conditions, and emotional needs received a lower consensus, suggesting the need for future research on holistic nursing care.